ANALISIS BAHAYA DAN IDENTIFIKASI TITIK KRITIS PADA INDUSTRI RUMAH TANGGA PEMBUATAN TAHU CINA DAN TAHU SUMEDANG DI KELURAHAN SARI REJO KECAMATAN MEDAN POLONIA - Rosalyn Sitinjak; Albiner Siagian; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Food secure is an important condition for food that will be consumed by society. Food insecurity can be happen on food processing process call critical point which is if uncontrolled can endanger society.   This research is observational survey with purpose to analize hazards and to know critical points in the making of Chinese Tofu and Sumedang Tofu at Kelurahan Sari Rejo, Kecamatan Medan Polonia. Data collecting done by observation and documentation Tofu making process.   The research result showing the existence of physic contamination such as sand and rotten soybean on Chinese Tofu and just rotten soybean found on Sumedang Tofu. Both of soybean soaking water containing E.coli. Undiscovered E.coli and also Salmonella on tofu. Curd material which is sulphate calcium exceed dose for making Chinese Tofu. Heavy metal (lead, copper, arsenic) at both of the tofu not exceed secure perimeter yet. Formalin positive at both of the tofu. Critical points at the making of Chinese Tofu are on soybean soaking, curd and printing. Critical point found for Sumedang Tofu processing process on soybean soaking.   Base of the observational result, producer expecting to using chemical material accords measuring, do not use harmfull chemical material. Utilizing clean water in production process and paying attention to equipment hygiene that is utilized and material those are utilized may not contaminate product that be endanger consumer.   Keywords: hazard analysis, critical point, Chinese Tofu, Sumedang Tofu, household food industry